Direct imaging of capillaries reveals the mechanism of arteriovenous interlacing in the chick chorioallantoic membrane. (December 2018) - Richard, Sophie; Brun, Amanda; Tedesco, Antonio; Gallois, Benjamin; Taghi, Naoual; Dantan, Philippe; Seguin, Johanne; Fleury, Vincent
Abstract Understanding vascular development in vertebrates is an important scientific endeavor. Normal vasculatures generally start off as a disorganized capillary lattice which progressively matures into a well-organized vascular loop comprising a hierarchy of arteries and veins. One striking feature of vascular development is the interlacing of arteries and veins. How arteries and veins manage to avoid themselves and interlace with such a perfect architecture is not understood. Here we present a detailed view of the development of the vasculature in the chorioallantoic membrane of the chicken embryo. We find that the origin of arteriovenous interlacing lies in the presence of an increased hemodynamic resistance at the distal part of the arteries due to vascular flattening onto the ectodermal surface. This reduces the vascular conductance distally, thus repelling veins away. In more proximal parts, vessels round off into cylinders and the increased flow attracts veins. Sophie Richard et al. present a detailed study of the development of the vasculature in the chicken embryo chorioallantoic membrane. They find that the interlacing of arteries and veins arises due to differential hemodynamic resistance acting on the distal and proximal ends of the arteries causing veins to be alternately repelled or attracted.